Impact of Robustness of Supply Chain on its Performance - An Empirical Study - Raj, K Bhavana; Srinivas, Kolachina (ExcelingTech, 2019)
Robustness of supply chain is rapidly expanding due to mitigation and reduction in the risk of unexpected and destructive events in the companies. As it is impossible for companies to resume their business post major crisis, the prediction of environmental factors that surround the companies paved way for development of a disaster recovery plan. 80% of the companies suffer from business interruptions and lack clarity in disaster management plan. A conceptual model was developed and validated based on supply chain management and supply chain robustness. A structured questionnaire was developed and administered to the supply chain managers. The survey data was collected from 126 organizations of the automotive sector. Structural equation modeling (SEM) techniques were employed to test the hypotheses. The study indicates that the robustness of Supply chain has a positive impact on the performance of the supply chain